The labrador pact eaudiobook - Haig, Matt (HighBridge Audio, 2008)
The story of a family in crisis and the loyal dog that holds them together, from the witty, imaginative author of The Dead Fathers Club. The Hunters-Adam, Kate, and their children Hal and Charlotte-are a typical family, with typical concerns: work, money, love, and the trials of adolescence. What sets them apart is Prince, their black labrador. Prince is an earnest and determined young dog. He strives to live up to the tenets of the Labrador Pact: Duty Over All. Other dogs, led by the springer spaniels, have revolted, but Prince takes his responsibilities seriously. As things in the Hunter family begin to go awry-marital breakdown, rowdy teenage parties, attempted suicide-he uses every canine resource to keep the clan together. In the end, Prince must choose: the family or the Pact? His decision may cost him everything. Wry, perceptive, and heartbreaking, The Labrador Pact is a cunning and original take on domestic life, with an improbably poignant narrator.